(untitled) (Baghdad Science Journal, 2024)
Zinc oxide nanoparticles were synthesized in a wet chemical manner at two different reaction temperatures 30, 90 ̊C utilizing zinc chloride as precursors in an aqueous medium. Zinc oxide nanoparticles were characterized by scanning electron microscopy (SEM), X-ray analysis (XRD), and infrared spectroscopy (FTIR). X-ray patterns pointed to a Wurtzite structure with an average crystalline size of 19.5 nm and 23 nm for the ZnO NPs synthesis at 30 ̊C and 90 ̊C, respectively. SEM showed that with increasing temperature, the morphology of Zinc oxide nanoparticles changed from nanowire to spherical structures. To fabricate super hydrophobic cotton fabric, the fabric was immersed in a colloidal solution of ZnO NPs with a concentration of 1% and then modified later with stearic acid. The samples were characterized by scanning electron microscopy (SEM) and contact angle (CA) test. The SEM results showed that the ZnO NPs synthesis at 90 ̊C created a rough structure on the cotton surface better than that of ZnO synthesis at 30 ̊C. The CA test showed super hydrophobic properties for ZnO@90˚C samples, while ZnO@30˚C samples showed hydrophobic properties only after modified stearic acid. Different stearic acid concentrations were used for the hydrophobization of the ZnO surface. (CA) results revealed that the fabric treated with ZnO NPs prepared at 90°C and modified with 1% by weight of stearic acid showed a superhydrophobic surface at a contact angle (CA = 154°).